Relationship of visually assessed apical rocking and septal flash to response and long-term survival following cardiac resynchronization therapy (PREDICT-CRT). (20th November 2015) - Stankovic, Ivan; Prinz, Christian; Ciarka, Agnieszka; Daraban, Ana Maria; Kotrc, Martin; Aarones, Marit; Szulik, Mariola; Winter, Stefan; Belmans, Ann; Neskovic, Aleksandar N.; Kukulski, Tomasz; Aakhus, Svend; et al.
Abstract: Aims: Apical rocking (ApRock) and septal flash (SF) are often observed phenomena in asynchronously contracting ventricles. We investigated the relationship of visually assessed ApRock and SF, reverse remodelling, and long-term survival in cardiac resynchronization therapy (CRT) candidates. Methods and results: A total of 1060 patients eligible for CRT underwent echocardiographic examinations before and 12 ± 6 months after device implantation. Three blinded physicians were asked to visually assess the presence of ApRock and SF before device implantation and also their correction by CRT 12 ± 6 months post-implantation. Patients with a left ventricular (LV) end-systolic volume decrease of ≥15% during the first year of follow-up were regarded as responders. Patients were followed for a median period of 46 months (interquartile range: 27–65 months) for the occurrence of death of any cause. If corrected by CRT, visually assessed ApRock and SF were associated with reverse remodelling with a sensitivity of 84 and 79%, specificity of 79 and 74%, and accuracy of 82 and 77%, respectively. ApRock (hazard ratio [HR] 0.40, 95% confidence interval [CI] 0.30–0.53, P < 0.0001) and SF (HR 0.45 [CI 0.34–0.61], P < 0.001) were independently associated with lower all-cause mortality after CRT and had an incremental value over clinical variables and QRS width for identifying CRT responders. Both the absence of ApRock/SF and unsuccessful correction of ApRock/SF despite CRT were associated with a high risk for non-response and an unfavourable long-term survival. Conclusion: A specific LV mechanical dyssynchrony pattern, characterized by ApRock and SF, is associated with a more favourable long-term survival after CRT. Both parameters are also indicators of an effective therapy.